Tsung-mi and the Sinification of Buddhism - Gregory, Peter N. (Kuroda Studies in East Asian Buddhism, 2023)
This study of Tsung-mi is part of the Studies in East Asian Buddhism series. Author Peter Gregory makes extensive use of Japanese secondary sources, which complements his work on the complex Chinese materials that form the basis of the study